Anaesthetic challenges for a patient with huge superior mediastinal mass in prone position - Yeap, Boon Tat; Teah, Kai Ming; Astrie Kamalia Mohd Ramly; Bong, Pei Chin (BMJ Publishing Group, 2021)
Anaesthesia for patients with huge mediastinal mass is very challenging due to the cardiorespiratory embarrassment that may occur. We present a patient with this condition, which was complicated by total airway obstruction, intraoperatively. We discuss the importance of patient positioning and the role of spontaneous ventilation.